Pedekatan Holistik Pasien Tuberkuloma Serebri Dalam Kehamilan: Laporan Kasus - Junita Indarti; Elizabeth Novita; Leonita Triwachyuni Agustina Sutrisna; Rendy Pratama (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Background: Tuberculoma are tumor-like space occupying lesions dispersed among various sites. Unlike pulmonary tuberculosis (TB), diagnosis and treatment of tuberculoma have received little consideration, especially those affected during pregnancy.Case: A 22-years-old women with two gestations, one parity, one abortion, and one alive child was admitted due to several syncope episodes. It was found that she had cerebral tuberculoma and received appropriate medication. Following her discharge, she was pregnant and had another symptoms. Holistic and multidiscipline approach was provided to the patient.Discussion: Cerebral tuberculoma is one of the most serious clinical forms of TB. There are some interactions between pregnancy and cerebral tuberculoma. Diagnosis and management on biopsychosocial aspect of cerebral tuberculoma in pregnancy was needed for patients, couples, and families affected.Conclusion: Tuberculoma in pregnancy is one of the challenging problem in pregnancy. Limited resource of references combined with both the mother and baby condition. It is important that healthcare providers assess the patient’s need and provide comprehensive and holistic management.